Nanocomposite of graphene and WO3 nanowires for carbon monoxide sensors. Issue 1 (2nd January 2021) - Estananto,; Septiani, Ni Luh Wulan; Iqbal, Muhammad; Suyatman,; Nuruddin, Ahmad; Yuliarto, Brian
Abstract: Due to its harmful nature, carbon monoxide (CO) should be detected at low temperature and in a wide range of CO concentration. A sensor based on WO3 –graphene nanocomposite synthesized by the solvothermal method has been developed. Based on material characterizations, the synthesized monoclinical WO3 has a nanowire shape. The presence of graphene interestingly promoted the formation of the WO3 hexagonal structure as a minor phase in the composite. The gas sensor measurements were carried out at three different temperatures, 300 °C, 150 °C, and room temperature. It was found that at 300 °C, the composite with ratio WO3 :graphene 2:1 or WG21 produces a 21.5 response value to 10 ppm of CO, which is higher than the other composites. The response and recovery times of WG21 are 16 and ∼4.4 min, respectively. The WG21 nanocomposite was also found to show a good sensitivity in the range concentration of 10–300 ppm. Graphical Abstract: UF0001